Causal relationship between gut microbiota with subcutaneous and visceral adipose tissue: a bidirectional two-sample Mendelian Randomization study - Cao, Feng; Pan, Feng; Gong, Xin; Wang, Wen; Xu, Yanyan; Cao, Pengwei; Wang, Yong (Frontiers in Microbiology, 2023)
Background Numerous studies have revealed associations between gut microbiota and adipose tissue. However, the specific functional bacterial taxa and their causal relationships with adipose tissue production in different regions of the body remain unclear. Methods We conducted a bidirectional two-sample Mendelian Randomization (MR) study using aggregated data from genome-wide association studies (GWAS) for gut microbiota and adipose tissue. We employed methods such as inverse variance weighted (IVW), MR Egger, weighted median, simple mode, and weighted mode to assess the causal relationships between gut microbiota and subcutaneous adipose tissue (SAT) as well as visceral adipose tissue (VAT). Cochran’s Q test, MR-Egger regression intercept analysis, and MR-PRESSO were used to test for heterogeneity, pleiotropy, and outliers of the instrumental variables, respectively. Reverse MR was employed to evaluate the reverse causal relationships between SAT, VAT, and gut microbiota with significant associations. Results IVW results demonstrated that Betaproteobacteria were protective factors for SAT production (OR = 0.88, 95% CI: 0.80–0.96, p = 0.005) and VAT production (OR = 0.91, 95% CI: 0.83–0.99, p = 0.030). Various bacterial taxa including Ruminococcaceae UCG002 (OR = 0.94, 95% CI: 0.89–0.99, p = 0.017), Methanobacteria class (OR = 0.96, 95% CI: 0.92–1.00, p = 0.029), and Burkholderiales (OR = 0.90, 95% CI: 0.83–0.98, p = 0.012) were associated only with decreased SAT production. Rikenellaceae RC9 gut group (OR = 1.05, 95% CI: 1.02–1.10, p = 0.005), Eubacterium hallii group (OR = 1.08, 95% CI: 1.01–1.15, p = 0.028), Peptococcaceae (OR = 1.08, 95% CI: 1.01–1.17, p = 0.034), and Peptococcus (OR = 1.05, 95% CI: 1.00–1.10, p = 0.047) were risk factors for SAT production. Meanwhile, Eubacterium fissicatena group (OR = 0.95, 95% CI: 0.91–0.99, p = 0.019), Turicibacter (OR = 0.93, 95% CI: 0.88–0.99, p = 0.022), and Defluviitaleaceae UCG011 (OR = 0.94, 95% CI: 0.89–0.99, p = 0.024) were protective factors for VAT production. Furthermore, Bacteroidetes (OR = 1.09, 95% CI: 1.01–1.17, p = 0.018), Eubacterium eligens group (OR = 1.09, 95% CI: 1.01–1.19, p = 0.037), Alloprevotella (OR = 1.05, 95% CI: 1.00–1.10, p = 0.038), and Phascolarctobacterium (OR = 1.07, 95% CI: 1.00–1.15, p = 0.042) were associated with VAT accumulation. Additionally, reverse MR revealed significant associations between SAT, VAT, and Rikenellaceae RC9 gut group (IVW: OR = 1.57, 95% CI: 1.18–2.09, p = 0.002) as well as Betaproteobacteria (IVW: OR = 1.14, 95% CI: 1.01–1.29, p = 0.029), both acting as risk factors. Sensitivity analyzes during bidirectional MR did not identify heterogeneity or pleiotropy. Conclusion This study unveils complex causal relationships between gut microbiota and SAT/VAT, providing novel insights into the diagnostic and therapeutic potential of gut microbiota in obesity and related metabolic disorders.